Down-Regulation of KORRIGAN-Like Endo-β-1,4-Glucanase Genes Impacts Carbon Partitioning, Mycorrhizal Colonization and Biomass Production in Populus - Kalluri, Udaya C.; Payyavula, Raja S.; Labbé, Jessy L.; Engle, Nancy; Bali, Garima; Jawdy, Sara S.; Sykes, Robert W.; Davis, Mark; Ragauskas, Arthur; Tuskan, Gerald A.; Tschaplinski, Timothy J. (Frontiers in Plant Science, 2016)
A greater understanding of the genetic regulation of plant cell wall remodeling and the impact of modified cell walls on plant performance is important for the development of sustainable biofuel crops. Here, we studied the impact of down-regulating KORRIGAN-like cell wall biosynthesis genes, belonging to the endo-β-1,4-glucanase gene family, on Populus growth, metabolism and the ability to interact with symbiotic microbes. The reductions in cellulose content and lignin syringyl-to-guaiacyl unit ratio, and increase in cellulose crystallinity of cell walls of PdKOR RNAi plants corroborated the functional role of PdKOR in cell wall biosynthesis. Altered metabolism and reduced growth characteristics of RNAi plants revealed new implications on carbon allocation and partitioning. The distinctive metabolome phenotype comprised of a higher phenolic and salicylic acid content, and reduced lignin, shikimic acid and maleic acid content relative to control. Plant sustainability implications of modified cell walls on beneficial plant-microbe interactions were explored via co-culture with an ectomycorrhizal fungus, Laccaria bicolor. A significant increase in the mycorrhization rate was observed in transgenic plants, leading to measurable beneficial growth effects. These findings present new evidence for functional interconnectedness of cellulose biosynthesis pathway, metabolism and mycorrhizal association in plants, and further emphasize the consideration of the sustainability implications of plant trait improvement efforts.